АРАЛ АПАТШЫЛЫҒЫНЫҢ ПАЙДА БОЛЫЎ СЕБЕПЛЕРИ - Абатов, А. (ILIM hám JÁMIYET, 2021)
The article discusses the reform of the agrarian sector by the totalitarian Soviet authorities, which caused the ecological problem of Central Asia as the drying up of the Aral Sea and its consequences.